Analysis of The Influence of Sharia Financial Institutions on Economic Growth in The Top Global Islamic Economy Index (GIEI) Countries - Leny Indahsari; Heni Noviarita; Muhammad Iqbal Fasa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The high level of Muslim growth has resulted in increased spending by Muslims on sharia goods or services. One of them is the increase in demand for sharia financial institutions in 2020/2021, which can be seen from the increase in performance, namely 17 billion or the equivalent of 246% from the previous year. The aim of this research is to determine and analyze the influence of sharia financial institutions on economic growth in 10 Global Islamic Economy Index (GIEI) countries. This research uses a descriptive quantitative research approach with spatial analysis in 2017-2022. The results of this research show that in the short and long term there is spatial dependence on economic growth in the 10 Global Islamic Index (GIEI) countries. The results of the spatial regression analysis show that the independent variables that have a significant influence are the asset value of sharia banks, the value of sukuk assets and the value of takaful assets with spatially correlated values ​​between regions. The asset value of sharia banks and sukuk has a positive effect, this is due to the implementation of the sharia system and the investment made by sharia banks and sukuk which can increase productivity and investment is dominated by sustainable development while takaful has a negative effect on economic growth, this is because most of the assets takaful is invested in the capital market and the public's literacy level regarding takaful is still low.